Kualitas Cake Dengan Variasi Tape Ketan Hitam (Oryza sativa var. glutinosa) Menggunakan Pewarna Bunga Telang (Clitoria ternatea L.) - Anisa Safira Kusuma Wardani; Sinung pranata; Yuliana Reni Swasti (Universitas Muhammadiyah Semarang, 2020)
Black sticky rice is potential food which can be used to source bioactive compounds, carbohydrate, antioxidant, and fiber. Activity of active compounds and nutrition which contained in food ingredient it can increase with fermentation. Black sticky tapai which has sour flavor it less liked by most people, so it needs to be processed by making cakes. This research purpose is to know the effect variation of wheat flour and black sticky tapai, and to know the best variation of wheat flour and black sticky tapai to physical, chemical, microbiological, and organoleptic. The research using different concentration of black sticky tapai, there are K (0:1), A (1:1), B (1:2), and C (1:3), and colorant of butterfly pea flower using the same concentration. The best result of this research is cake with concentration B (1:2). Result showed that cake with concentration B (1:2) was contained 33,00 % water content, 1,37 % ash content, 19,72 % fat content, 7,70 % proteins content, 38,43 % carbohydrate content, 0,48 mg GAE/g phenolics content, 24,62 % antioxidant content, 158 g texture analysis, cake has white color, 5,20 log CFU/g total plate count, and 3,23 log CFU/g yeast molds.